Long-term cattle manure addition enhances soil-available phosphorus fractions in subtropical open-field rotated vegetable systems - Mao, Yanting; Hu, Wei; Li, Yongmei; Li, Yuan; Lei, Baokun; Zheng, Yi (Frontiers in Plant Science, 2023)
Phosphorus (P) components, and their availability at different soil layers, can be affected by long-term cattle manure application. This can further affect P uptake and environmental sustainability. However, changes in P components at different soil layers in response to cattle manure (M), as well as a combined cattle manure and chemical fertilizer application (M+F), remain unclear in open-field vegetable systems. If the amount of annual P input remains the same, then identifying which treatment would cause a higher phosphate fertilizer utilization efficiency (PUE) and vegetable yield, while simultaneously reducing the P surplus, is especially warranted. Based on a long-term manure experiment that started in 2008, we used a modified P fractionation scheme to analyze P components at two soil layers for three treatments (M, M+F, and control without fertilizer application) in an open-field cabbage (Brassica oleracea) and lettuce (Lactuca sativa) system during 2020 and 2022, and assessed the PUE and accumulated P surplus. The concentrations of the soil P components were higher in the 0–20 cm soil layer compared to 20–40 cm, except for organic P (Po) and residual-P. Cattle manure application significantly increased inorganic P (Pi) and Po content. Compared with the control and M+F treatments, M significantly increased residual-P, Resin-P, and NaHCO3-Pi at both soil layers, while NaOH-Pi and HCl-Pi at 0–20 cm were positively correlated with available P. Soil moderately labile-P was the predominant P component in the two soil layers. With the same annual P input amount, M+CF created the highest vegetable yield and PUE, and M created the highest accumulated P surplus. Collectively, a combined manure-chemical fertilizer application has great potential to yield a long-term positive outcome both in terms of vegetable productivity and environmental health in open-field vegetable systems. This highlights the methods’ benefits as a sustainable practice in subtropical vegetable systems. Specific attention should be given to a P balance to avoid excessive P input if a rational strategy for manure application is to be attained. This is especially true for stem vegetables that require manure application, and decreases the environmental risk of P loss in vegetable systems in China.